Corporate Social Responsibility and Leverage Level on High Profile Industries at Indonesian Stock Exchange of 2015-2019 Period - Inggrit Wijaya, Liliana; Herlambang, Arif; Evans, Billy (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2022)
This study aims at analyzing the effect of corporate social responsibility (CSR) and the level of use of debt on financial performance. The variables used in this study included corporate social responsibility, debt, age, size and employees. This study uses a quantitative paradigm with the least square regression panel data processing method. The population in this study is all non-financial sector companies included in the high profile industry category at the Indonesia Stock Exchange (ISE) for the 2015-2019 period. The results prove that CSR has a significant positive effect on financial performance as proxied by Tobin's Q. When a company's CSR is high, it will have a positive impact on its financial performance. Then, leverage has a negative effect on the performance because the higher the debt, the lower the company's performance.